2007
DOI: 10.1111/j.1750-3639.2006.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Hypermethylation of p14ARF and O6‐methylguanine‐DNA Methyltransferase Genes in Astrocytoma Progression

Abstract: The aim of the present study was to elucidate genetic alterations that are critically involved in astrocytoma progression. We characterized 27 World Health Organization grade II fibrillary astrocytomas which later underwent recurrence or progression, paying specific attention to the CpG island methylation status of critical growth regulatory genes. p14(ARF) and O(6)-methylguanine-DNA methyltransferase (MGMT) hypermethylation represented frequent events (26% and 63%, respectively), which were mutually exclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 24 publications
(52 reference statements)
2
35
0
1
Order By: Relevance
“…A methylation of DNA regulatory elements -mainly promoters, is one of the mechanisms of tumour suppressor genes silencing (Watanabe et al, 2007). It was shown that a similar proportion of gliomas with and without P53 mutation present P53 promoter methylation (Amatya et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A methylation of DNA regulatory elements -mainly promoters, is one of the mechanisms of tumour suppressor genes silencing (Watanabe et al, 2007). It was shown that a similar proportion of gliomas with and without P53 mutation present P53 promoter methylation (Amatya et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Exons 5 -8 of the P53 gene were amplified by PCR as described before and sequenced using the dideoxy termination method and SequiTherm Excel DNA Sequencing Kit (Epicentre Technologies) (Zakrzewska et al, 2005).…”
Section: P53 Dna and Cdna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, all secondary GBM (4/4) showed a methylated MGMT promoter and an unmethylated p15 promoter which underlines that distinct molecular pathways constitute the primary and the secondary glioblastomas and are responsible for their different biological behavior and in clinical outcome. This corresponds to the finding that methylation of MGMT promoter is mutually exclusive of p14 ARF methylation and the latter is associated with a shorter patient survival, except in one case of low grade astrocytoma who underwent progression or recurrence (38).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of p14 ARF has been associated with progression of astrocytomas (Watanabe et al, 2007) and has been described as a factor of poor prognosis of grade II diffuse gliomas (Watanabe et al, 2003), although its prognostic value in oligodendroglioma is more controversial (Korshunov and Golanov, 2001;Kamiya and Nakazato, 2002). p16 INK4A deletion is a factor of poor prognosis of these tumours (Jeon et al, 2007).…”
Section: Expressionsmentioning
confidence: 99%